Use of the “L-E-M-O-N” Score in Predicting Difficult Intubation in Africans - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Endotracheal intubation is an integral part of airway management and is key to the practice of safe anesthesia. Prediction of a difficult airway can help reduce the incidence of failed or difficult intubation. We studied the use of “L-E-M-O-N” (Look-Evaluate-Mallampati-Obstruction-Neck mobility) scoring system to predict difficult intubation and determine the prevalence of difficult intubation among adult surgical patients.Materials and Methods:One hundred and sixty (160) consecutive ASA I–III surgical patients between 18 and 65 years of age were recruited from October to December 2011. A variety of airway tests using the “L-E-M-O-N” scoring were done during preoperative assessment; and at induction of anesthesia, airway assessment using Cormack and Lehane was performed and the results were recorded by a standardized record sheet. The variables evaluated were gender, age, weight, height, body mass index (BMI), dentition and a variety of airway tests using the “L-E-M-O-N” scale. SPSS version 17.0 was used for statistical analysis; and aPvalue